The Effect of Motivation-Opportunity-Ability (MOA) Framework in SME's Social Media Marketing Adoption - Aulia Hadining (International Journal of Innovation in Enterprise System, 2020)
This research aimed to find out the factors which affected UKM/SME (small and medium sized enterprises) in adopting Facebook Ads. The factors utilized adoption model which has been developed in previous research by inserting Opportunity and Ability factors as a moderating effect between the influence of intention to use facebook ads toward the adoption of facebook ads. The background of this study was the need for the demand for the use of information technology, especially social networking in SME communication with consumers. This was intended to make SMEs survive in current technological developments. The model used in this research consisted of ten variables with nine hypotheses. Based on a survey of 100 SMEs in Indonesia, it was found that social image and perceived usefulness had a positive influence on intention to use Facebook Ads. However, there was no moderation effect from the Opportunity and Ability variable groups toward the relationship between Intention to use Facebook ads to Facebook Ads Adoption.